Risk assessment of inferior alveolar nerve injury for immediate implant placement in the posterior mandible: A virtual implant placement study - Lin, Ming-Hung; Mau, Lian-Ping; Cochran, David L.; Shieh, Yi-Shing; Huang, Po-Hsien; Huang, Ren-Yeong (Journal of dentistry, 2014)
To investigate the prevalence and morphological parameters of lingual concavity, and whether these factors are related to a higher risk of inferior alveolar nerve (IAN) injury when performing an immediate implant surgery in posterior mandible region. The CBCT images from 237 subjects (1008 teeth) were analysed the shape of the mandibles (C, P, U type), dimensional parameters of lingual concavity (angle, height, depth), and its relation to inferior alveolar canal (IAC) (A, B, C zone), RAC (distance from root apex to IAC) and probability of IAN injury. Multiple logistic regression modelling to determine the odds ratio of variables that made an important contribution to the probability of IAN injury and to adjust for confounding variables. The U type ridge (46.7%) and the most concave point located at C zone (48.8%) are most prevalent in this region. The mandibular second molar presents highest risk for IAN injury than other tooth type (p<0.001), which were 3.82 times to occur IAN injury than the mandibular second premolar. The concave point located at A zone and B zone were 7.82 and 3.52 times than C zone to have IAN damage, respectively. The probability of IAN injury will reduce 26% for every 1mm increase in RAC (p<0.001). The tooth type, morphological features of lingual concavities, and RAC are associated with risks of IAN injury during immediate implant placement. Pre-surgical mapping of the IAC and identification of its proximity relative to the lingual concavity in the posterior mandible regions may avoid unpleasant complications, specifically when performing immediate implant procedures.